„Novus ordo seclorum”: new applications of monoclonal antibodies in breast cancer - Duchnowska, Renata; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2005)
Trastuzumab (Herceptin) is a recombinant humanized monoclonal IgG1 antibody inhibiting selectively HER2 receptor in tumour cells, that has found a clinical application in breast cancer treatment. Until recently, this compound has been used exclusively in advanced breast cancer patients. During the 2005 Annual Meeting of the American Society of Clinical Oncology (ASCO) preliminary results of three large randomized studies were presented in which trastuzumab in combination with chemotherapy was administered in the adjuvant setting in operable breast cancer patients with HER2 expression or amplification. Two of these studies (NSABP-31 and NCCTG-N9831) were performed by the American cooperative groups: the National Surgical Adjuvant Breast and the Bowel Project (NSABP) and the North Central Cancer Treatment Group (NCCTG), and the third one (HERA) was a global enterprise coordinated by the Breast Intergroup (BIG) in Brussels. The presented results demonstrated a surprisingly positive impact of trastuzumab: the relative risk of disease failure was halved and additionally, in the two American studies the risk of death was significantly reduced. The treatment was well tolerated and the only serious adverse side effect was an increased risk of cardiotoxicity. At the same session, results of the first study of the third phase were presented showing a significant increase of time to progression associated with the addition of antiangiogenic monoclonal antibody – bevacizumab to standard chemotherapy of advanced breast cancer. This article presents the result of these studies and discusses their potential implications on changing standards of care in breast cancer.